A Technical Approach for Transfemoral Managing of Hostile Angulated Pelvic Vessel Access in Abdominal Endovascular Aneurysm Repair: A New Technique for Establishing a Buddy Wire - Ketelsen, D.; Bail, D.; Heuschmid, M.; Thomas, C.; Heller, S.; Claussen, C. D.; Brechtel, K. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: Endovascular aneurysm repair (EVAR) can be challenging in angulated access vessels. The aim of this study was to evaluate a new wire technique for installing a buddy wire in the event of failure of simple advancing of a super stiff guide. Materials and Method: We investigated 8 patients eligible for EVAR. All patients presented with heavily kinked pelvic access and failure of primary advancing of a stiff guide wire through a placed catheter. A double wire technique with a combination of soft and stiff wires was applied to place a super stiff buddy wire. Cumulative angulation quantified by the sum of angles of the tortuous pelvic access vessels was measured in pre- and post-interventional CT as well as in angiographic studies of the EVAR procedure. Patients were followed up on by CT in the first 6 months. Results: A buddy wire could be installed in all patients (100 %) with significant straightening of the access vessel from a median cumulative angulation of 252.4 ± 38.1° before intervention to 159.4 ± 44.6° after placement of the buddy wire (p < 0.001). There was no technical failure of device passage and all stent-grafts could be deployed safely. Three cases of stenosis caused by torsion distal to the aortic stent-graft were seen after stent-graft delivery. One case of stenosis was hemodynamically relevant and was successfully stented. No major adverse events occurred within the first 6 months of follow-up. Conclusion: The new step-by-step wire technique is feasible and safe in the case of hostile pelvic vessel access, and facilitates the advancement of aortic stent-grafts in off-label patients.
Keywords: aorta; angiography; interventional procedures; stents; aneurysm; technical aspects